Diversity of fig glands is associated with nursery mutualism in fig trees. Issue 10 (29th September 2015) - Souza, Camila D.; Pereira, Rodrigo A. S.; Marinho, Cristina R.; Kjellberg, Finn; Teixeira, Simone P.
Abstract : PREMISE OF THE STUDY: Fig trees (Moraceae) have remarkable enclosed inflorescences called figs or syconia. The flowers are pollinated by host‐specific fig wasps that enter the fig to lay their eggs. This nursery pollination system is one of the most studied of tropical mutualism interactions, but the source of the volatiles that attract fig wasps to their specific host figs has not been confirmed. The fragrance is the basis of host selection and, therefore, of reproductive isolation among sympatric Ficus species. This study locates and characterizes the glands likely to be responsible for pollinator attraction and also protection from herbivory in the figs of nine Ficus species representing all the major lineages within the genus. METHODS: Figs with receptive pistillate flowers were examined using light and scanning electron microscopy. Tests for histolocalization of substances were employed to detect glandular activity throughout the figs. KEY RESULTS: A great diversity of glands is found throughout the fig, and for the first time, the sites producing fragrances are identified. Scent glands are present on the ostiolar bracts and the outer layers of the fig receptacle. Laticifers and phenolic‐producing idioblasts, epidermis, and trichomes associated with fig protection occur on the ostiolar bracts, the fig receptacle, and floral tissues. CONCLUSIONS: The volatiles produced by glands on the ostiolar bracts are candidate sources for the long‐distance attraction of pollinator fig wasps. Scent glands on the outer layers of the receptacle may also play a role in chemical perception of the figs or may be related to their protection. The high cost to the plants if the figs are eaten and the temperature conditions required for nursery pollination are likely the factors that led to the selection of phenolic glands and laticifers during the group's evolution.